Pest categorisation of Penthimiola bella. (10th November 2022) - ; Bragard, Claude; Baptista, Paula; Chatzivassiliou, Elisavet; Di Serio, Francesco; Gonthier, Paolo; Jaques Miret, Josep Anton; Justesen, Annemarie Fejer; Magnusson, Christer Sven; Milonas, Panagiotis; Navas‐Cortes, Juan A; Parnell, Stephen; et al.
Abstract: The EFSA Panel on Plant Health performed a pest categorisation of Penthimiola bella (Hemiptera: Cicadellidae), the citrus leafhopper, for the European Union (EU). P. bella is native to the Afrotropical region; it has spread to Israel (first reported in 1974), Lebanon, and was reported from Morocco in 2018. Within the EU, P. bella is established in Portugal (Algarve) where it was first found on sweet oranges in 2012, and then in Spain in 2020, also on sweet oranges. P. bella is not listed in Annex II of Commission Implementing Regulation (EU) 2019/2072. It is a polyphagous species reported, among cultivated hosts, on sweet orange, grapefruit and avocado. It is also described as being found on unspecified trees and bushes in savannahs, mountain forests and rain forests in Africa. Climatic conditions in some parts of southern EU countries are favourable and host plants are available in those areas to support establishment and spread. Despite being present in Portugal for over 10 years, there is a lack of evidence of impacts; hence, the magnitude of impact following introduction is uncertain. Nevertheless, in South Africa, P. bella was reported as being an economically important pest of citrus and to cause damage to avocado fruit during the early stages of development. Phytosanitary measures are available to reduce the likelihood of entry and further spread. Except for having uncertain economic or environmental impacts as a result of its introduction, P. bella satisfies all the other criteria that are within the remit of EFSA to assess for it to be regarded as a potential Union quarantine pest.